2018
DOI: 10.1016/j.ijdevneu.2018.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral, cognitive and histological changes following neonatal anoxia: Male and female rats' differences at adolescent age

Abstract: Neonatal anoxia induces long‐term brain injury that may underlie neurobehavioral deficits at adolescence. Neonatal anoxia, induced by exposure of 30‐hour old pups to 100% nitrogen, represents a non‐invasive and global stimulus, which simulates clinical conditions of human pre‐term babies (around 6 gestational months). Previous studies showed that neonatal anoxia induced impairments of spatial memory and altered anxiety‐like behaviors in male rats tested at adult age. This study evaluated if neonatal anoxia ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 60 publications
1
14
0
2
Order By: Relevance
“…In general, hypoxia due to global ischemia leads to infarction which can damage the pyramidal neurons of the hippocampus, cerebral cortex, and necrosis of the basal ganglia [98]. In experimental models, histologic analysis indicates a shrunken eosinophilic neuron (anoxic neuron) and a red neuron, a representation of dead neuronal cells due to hypoxia [99].…”
Section: Viral Infection-induced Hypoxia and Brain Damagementioning
confidence: 99%
“…In general, hypoxia due to global ischemia leads to infarction which can damage the pyramidal neurons of the hippocampus, cerebral cortex, and necrosis of the basal ganglia [98]. In experimental models, histologic analysis indicates a shrunken eosinophilic neuron (anoxic neuron) and a red neuron, a representation of dead neuronal cells due to hypoxia [99].…”
Section: Viral Infection-induced Hypoxia and Brain Damagementioning
confidence: 99%
“…Neonatal hypoxia‐ischemia (Vannucci and Vannucci, 2005; Levine, 1960), perinatal asphyxia (Barkhuizen et al, 2017) and neonatal anoxia (Takada et al, 2011) in rats are included in the most often used models in newborns. Neonatal anoxia in rats causes loss in neuronal and glial populations in brain areas, cognitive and behavioral deficits (Takada et al, 2016, 2015; Kumar et al, 2017, 2019), delay in sensorimotor development and changes in somatic growth (Kumar et al, 2017). Body composition measures and neurodevelopmental disorders are also observed in human beings (Lip et al, 2018; Brooks et al, 2011; Strand et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Growth and body weight modifications in children with neurodevelopmental disorders following oxygen deficiency have been reported (Lip et al, 2018;Brooks et al, 2011;Strand et al, 2016). Likewise, previous experimental studies have showed that neonatal oxygen deprivation impairs the somatic development of Wistar rats (Kumar et al, 2019;Shimomura and Ohta, 1988;Tang and Nakazawa, 2005;Grojean et al, 2003;Yan et al, 2016). However, little is known about the causes of these alterations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research conducted in our laboratory also evaluated the effects of anoxia in adolescence on the cell count of other encephalic regions (Kumar et al, 2020(Kumar et al, , 2019. The hippocampus analysis showed different results according to the considered subfield, which also might be related to their developmental stage: in CA1, anoxia males and females presented fewer cells than their controls; however, at the dentate gyrus, only anoxia males presented fewer cells than their control (Kumar et al, 2019). The same results were observed in thalamic ventral posterolateral nuclei (Kumar et al, 2020).…”
Section: Discussionmentioning
confidence: 99%